The means - Fusselman, Amy (Mariner Books, 2022)
"The debut novel from "wholly original" (Vogue) memoirist Amy Fusselman, a tragicomic family saga that skewers contemporary issues of money, motherhood, and class through a well-to-do woman's quest to buy a Hamptons beach house"--